Implementation of Door Lock System Using Keyword and RFID - Suwanty, Erina; Hidayati, Rahmi; Sari, Kartika (Digital Innovation, 2025)
Doors are an important element in a building that serve as a connection between rooms. Generally, door locking systems are still conventional, which have several shortcomings, such as being easy to duplicate. Therefore, this study developed a door locking system using a keyword and RFID (Radio Frequency Identification), as combining two security systems enhances security quality. Testing was conducted by collecting data on the performance of the Voice Recognition module at randomly selected distances ranging from 20 to 100 cm, with intervals of 20 cm between the user's voice and the microphone. Then, the RFID capability was tested under two different conditions: the first condition where the RFID card was not covered by a cover, and the second condition using a cover to simulate the condition of the card being inside a wallet or case, and finally, the overall system testing. Based on the test results conducted in this study, using both sensors with a total of 40 data points, the overall system achieved 100% accuracy.